Asymmetric Iodolactonization: An Evolutionary Account. Issue 15 (11th February 2014) - Nolsøe, Jens M. J.; Hansen, Trond V.
Abstract: The diversity entailed by halolactonization makes it a fundamental transformation, enabling the synthetic organic chemist to build up molecular complexity in a way that relates structural elements in a predictable manner. Due to practical aspects and the subsequent flexible manipulation of the installed halogen handle, iodolactonization takes precedence over the other variants. The asymmetry that can be conferred on the products by iodine‐induced cyclization has been the subject of various approaches. For a long time stereoselectivity has been achieved by substrate‐controlled reactions. However, lately, the reagent‐controlled counterpart has surfaced as an alternative based on the action of a catalyst. Despite the fact that the current progress in catalytic asymmetric iodolactonization has happened only in the space of the last three years, a number of conceptually different approaches have already been applied to advance beyond the substrate‐controlled reaction. Herein we describe the various strategies, which have propelled the development of asymmetric iodolactonization to its current state, putting an emphasis on catalysis. Abstract : Iodolactonization is a valuable synthetic tool owing to the inherent stereochemical nature of the process. From a substrate perspective, the asymmetric reaction has been pursued with great zeal. In contrast, moving beyond the chiral environment offered by the prospective ring has long been neglected. However, in the last three years several highly enantioselective catalytic protocols have emerged.